Serological diagnosis of syphilis - Simčič, Saša (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2015)
Introduction: Serological tests' limitations in syphilis diagnosis as well as numerous test interpretations mean that patients with discordant serology results can present diagnostic and treatment challenges for clinicians. We analyzed three common diagnostic algorithms for detecting suspected syphilis in high-prevalence populations in Slovenia. Methods: The prospective study included a total of 437 clinical serum samples from adults throughout Slovenia tested with Rapid Plasma Reagin (RPR), Treponema pallidum hemagglutination (TPHA), and an automated chemiluminescence immunoassay (CIA) according to the manufacturer's instructions. In addition to percent agreement, kappa coefficients were calculated as a secondary measure of agreement between the three algorithms. Results: Overall, of 183 subjects that had seroreactive results, 180 were seroreactive in both the reverse sequence and the European Centre for Disease Prevention and Control (ECDC) algorithm. The traditional algorithm had a missed serodiagnosis rate of 30.0%, the overall percent agreement between the traditional and the reverse algorithm (or the ECDC algorithm) was 87.6%, and the kappa value was 0.733. However, the reverse and ECDC algorithm failed to detect three subjects with positive serodiagnosis determined by additional confirmative treponemal assays. Conclusions: Our results supported the ECDC algorithm in the serodiagnosis of syphilis in high-prevalence populations and the use of nontreponemal serology to monitor the response to treatment.
Keywords: diagnostics; diagnostika; sexually transmitted infections; sifilis; spolno prenosljive okužbe; syphilis